Amounts of the reactive aldehydes, malonaldehyde, 4‐hydroxy‐2‐hexenal, and 4‐hydroxy‐2‐nonenal in fresh and oxidized edible oils do not necessary reflect their peroxide and anisidine values. Issue 3 (26th November 2015) - Viau, Michèle; Genot, Claude; Ribourg, Lucie; Meynier, Anne
Abstract : There is a growing development of foods and food supplements enriched in n‐3 lipids, whereas quantitative data on oxidation products present throughout the food chain are lacking. To give a first insight of the range of potentially toxic aldehydes that can be encountered in these foods, malondialdehyde (MDA), 4‐hydroxy‐2‐hexenal (4‐HHE) and 4‐hydroxy‐2‐nonenal (4‐HNE) were quantified in a set of four fresh and oxidized oils presenting large variations in unsaturation levels, n‐6/n‐3 ratio and oxidabilities. Results were compared to classical methods. In fresh rapeseed, sunflower, kiwiseed, and tuna oils, the concentrations of MDA ranged between 0.6 and 29 μmol kg −1 oil, of hydroxyalkenals between 0.1 and 3.3 μmol kg −1, hydroperoxides concentrations (HPX) ranged between 0.4 and 4 mmol kg −1 oil, peroxide value (PV) and anisidine value (AV) were well below the acceptable limits. In oxidized rapeseed, kiwiseed, and tuna oils 4‐HHE ranged from 120 to 150 μmol kg −1, whereas MDA ranged from 600 to above 1100 μmol kg −1 . Conversely, sunflower oil exhibited the highest quantities 4‐HNE (175 μmol kg −1 ) but the lowest of MDA (100 μmol kg −1 ) and 4‐HHE (2.9 μmol kg −1 ) in agreement with its fatty chain composition. Altogether, the results highlight the interest of using methods able to quantify specific oxidation products and not only PV and AV to assess lipid oxidation especially in oils or products containing high quantities of n‐3 FA. Practical applications: This work provides quantitative data regarding amounts of toxic aldehydes that can be present in edible oils. The used methods made it possible to quantify MDA, 4‐HNE, and 4‐HHE as respective markers of oxidation of polyunsaturated fatty acids in a whole, n‐6 and n‐3 polyunsaturated fatty acids. They could be applied to oils, fats, and food products to better estimate the occurrence and exposure to these compounds. Comparison with methods currently used to evaluate the quality of edible oils indicates clearly that the dynamics of formation of the different oxidation markers are oil‐specific. Thus, oxidation indicators should be selected as regard to fatty chain profiles and not used to compare oils with very different profiles of polyunsaturated fatty acids .These tools could be used to design nutritional, metabolic, and toxicological trials avoiding too unrealistic exposures in undesirable contaminants. MDA, 4‐HNE, and 4‐HHE were quantified in fresh and oxidized rapeseed, sunflower (S), kiwiseed (K) and tuna oils (T), together with classical (R) markers such as PV or CD. In fresh oils, MDA ranged from 0.6 up to 29 µmol kg −1 oil, whereas 4‐HNE and 4‐HHE were closed to 1 µmol kg −1 oil whatever the oil, excepted in fresh kiwiseed oil (3.3 µmol kg −1 oil). MDA was the major secondary product in highly oxidized oils except in sunflower oil. Its quantities ranged from 100 µmol kg −1 in sunflower up to 1.1 mmol kg −1 in kiwiseed oil. 4‐HNE is the major secondary product in sunflower oil (170 µmol kg −1 ), while 4‐HHE ranged from 120 to 150 µmol kg −1 in n‐3 containing oils. The evolution of marker profiles is oil‐specific. Abstract : MDA, 4‐HNE, and 4‐HHE were quantified in fresh and oxidized rapeseed, sunflower (S), kiwiseed (K) and tuna oils (T), together with classical (R) markers such as PV or CD. In fresh oils, MDA ranged from 0.6 up to 29 µmol kg −1 oil, whereas 4‐HNE and 4‐HHE were closed to 1 µmol kg −1 oil whatever the oil, excepted in fresh kiwiseed oil (3.3 µmol kg −1 oil). MDA was the major secondary product in highly oxidized oils except in sunflower oil. Its quantities ranged from 100 µmol kg −1 in sunflower up to 1.1 mmol kg −1 in kiwiseed oil. 4‐HNE is the major secondary product in sunflower oil (170 µmol kg −1 ), while 4‐HHE ranged from 120 to 150 µmol kg −1 in n‐3 containing oils. The evolution of marker profiles is oil‐specific.